2000
DOI: 10.1093/ajcn/72.2.378
|View full text |Cite
|
Sign up to set email alerts
|

Early risk factors for increased adiposity: a cohort study of African American subjects followed from birth to young adulthood

Abstract: Background:Obesity is an increasing concern in the United States. Effective prevention of obesity requires the risk factors to be well defined. African Americans have a high risk of obesity. Objective: The objective of this study was to identify risk factors, present at birth, for increased adiposity in adulthood in an African American population. Design: In this retrospective analysis of a prospective cohort study, anthropometric and socioeconomic variables were collected at birth. A representative sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
5
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 37 publications
7
106
5
2
Order By: Relevance
“…According to our study, being a firstborn was the aspect that proved to affect overweight or obese status, as there was no difference in comparison to being a single child. Association of firstborn status and risk of obesity has been reported by other studies (Stettler et al, 2000), and has been attributed to potential factorsFnot yet identified wellFconnected to gestational period, postnatal period or both.…”
Section: Discussionmentioning
confidence: 78%
“…According to our study, being a firstborn was the aspect that proved to affect overweight or obese status, as there was no difference in comparison to being a single child. Association of firstborn status and risk of obesity has been reported by other studies (Stettler et al, 2000), and has been attributed to potential factorsFnot yet identified wellFconnected to gestational period, postnatal period or both.…”
Section: Discussionmentioning
confidence: 78%
“…Experimental studies in humans are rare, but observational studies in humans have shown that gestational diabetes or excessive gestational weight gain is associated with fetal overnutrition and elevated birth weight, which predict later offspring obesity; elevated maternal pre-pregnancy weight status is also positively associated with higher birth weight and later obesity risk. [33][34][35][36][37] Cole and colleagues 38 describe two ways to end up with an overweight phenotype: by starting out large or by growing fast. Links between fetal overnutrition and obesity risk take on particular significance in countries where obesity is prevalent among adult women of childbearing age, as in the United States, where two-thirds of adults are overweight or obese, 39 and gestational weight gain guidelines are frequently exceeded.…”
Section: Prenatal Periodmentioning
confidence: 99%
“…For example, fetal growth is impaired in those who are born to smaller mothers, to primigravida, or to very young mothers; this is sometimes termed 'maternal constraint'. Thus, first-born children may be at particular risk 40 and demographic changes that have led to a decrease in family size mean that the proportion of first-born children in the population has increased. Similarly, there is evidence that variation in maternal nutrition within the usual range of intakes of Western women can affect fetal physiology, size at birth and subsequent endothelial function in childhood.…”
Section: The 'Mismatch' or 'Thrifty' Pathwaymentioning
confidence: 99%
“…The model can explain a number of apparently puzzling features of the demography of obesity, such as the rapid appearance in populations undergoing the nutrition transition 72 and the higher incidence in first-born children. 40 A particular concern arises from observations that for cultural and socioeconomic reasons women even in developed countries may not receive optimal nutrition during pregnancy. In Japan, birth weight is falling in parallel with a reduction in maternal weight gain, in part because of an unsubstantiated belief that dietary restriction of weight gain improves pregnancy outcome.…”
Section: The 'Mismatch' or 'Thrifty' Pathwaymentioning
confidence: 99%